2009
DOI: 10.1039/b817728g
|View full text |Cite
|
Sign up to set email alerts
|

Facile dichloromethane activation and phosphine methylation. Isolation of unprecedented zwitterionic organozinc and organocobalt intermediates

Abstract: Both C-Cl bonds of CH(2)Cl(2) are readily activated by CoCl(2) and metallic Zn allowing quantitative methylation of phosphines; unprecedented zwitterionic Co(ii) and Zn(ii) intermediates have been characterized which display alpha-metallated phosphoniums.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 38 publications
1
25
0
Order By: Relevance
“…[15] The formation of these chloride species in the presence of Au I is also possible even at room temperature instead of 50 8C. There is some precedent for the facile activation of CH 2 Cl 2 in the presence of transition metals, such as Zn or Co, [16] Rh, [17] and Mg/TiCl 4 /THF, [18] but as far as we know, the instability of CH 2 Cl 2 was not detected previously with 2-di-tert-butylphosphanylbiphenyl Au I or Cu I complexes as catalysts. We tested the catalytic activity of this neutral gold(I) complex [LAuCl] (10; Table 1, entries 5 and 6) for the Mannich A 3 coupling and found that it was considerably less active than the initial precatalyst Cu I complexes 3 and 5 and the Au I complexes 6 and 7.…”
Section: Methodsmentioning
confidence: 99%
“…[15] The formation of these chloride species in the presence of Au I is also possible even at room temperature instead of 50 8C. There is some precedent for the facile activation of CH 2 Cl 2 in the presence of transition metals, such as Zn or Co, [16] Rh, [17] and Mg/TiCl 4 /THF, [18] but as far as we know, the instability of CH 2 Cl 2 was not detected previously with 2-di-tert-butylphosphanylbiphenyl Au I or Cu I complexes as catalysts. We tested the catalytic activity of this neutral gold(I) complex [LAuCl] (10; Table 1, entries 5 and 6) for the Mannich A 3 coupling and found that it was considerably less active than the initial precatalyst Cu I complexes 3 and 5 and the Au I complexes 6 and 7.…”
Section: Methodsmentioning
confidence: 99%
“…At the beginning of a comprehensive study of the in uence of various anions on bond lengths and angles among a series of tetraorgano phosphonium compounds, the title was synthesized. Crystal and molecular structures of several tetrachloridozincate(II) anions with tetraorganophosphonium counterions such as trimethylphenylphosphonium [1], methyltriphenylphosphonium [1] or tetraphenylphosphonium [2] as well as tetrabromidozincate(II) anions with tetraorganophosphonium counterions such as methyltriphenylphosphonium [3], tetraphenylphosphonium [2] or methylenebis(triethylphosphonium) [4] In the crystal, C-H· · · Br contacts can be observed whose range falls below the sum of van-der-Waals radii of the atoms participating in them [6]. These are exclusively supported by one of the aromatic hydrogen atoms in ortho-position to the phosphorus atom as well as one of the hydrogen atoms of the methylene group in each of the two cations as donors but only two of the bromido ligands as acceptors.…”
Section: Discussionmentioning
confidence: 99%
“…4 Easy activation of both C-Cl bonds of CH 2 Cl 2 by CoCl 2 and metallic Zn allowed quantitative methylation of aromatic and aliphatic phosphines in air to afford (R 3 P þ Me) 2 (ZnCl 4 ) species or, in the case of phosphino-substituted oxa(-thia)zolines, zwitterionic complexes (6) with a negatively charged ZnCl 3 group. 5 The bromide salts [R 3 P-P(R') 2= NSiMe 3 ]Br [(7), R 0 = Me, OCH 2 CF 3 ; R 3 P = Me 3 P, Et 3 P, nBu 3 P, dmpm (dmpm = dimethylphosphinomethane, dmpe = dimethylphosphinoethane)] of phosphine-stabilized phosphoranimine cations, were prepared from the direct reactions between BrMe 2 P = NSiMe 3 and Br(CF 3 CH 2 O) 2 P = NSiMe 3 and the corresponding tertiary phosphines R 3 P or diphosphines Me 2 P(CH 2 ) n PMe 2 . The anion exchange reactions between the bromide salts and AgOTf quantitatively afforded the more stable triflate salts.…”
Section: Preparationmentioning
confidence: 97%
“…120 For subsequent introduction of a series of double bonds the Wittig olefination can be used more than once. For example, preparation of functionalized [5]-and [6]-carbohelicenes required two subseqent Wittig reactions. 121 The Wittig reaction, followed by Horner-Wadsworth-Emmons olefination, was used in the synthesis of phosphonium salt (70) subsequent Wittig olefination of which with a substituted pyrancarboxaldehyde provided the PMB-protected interemediate (Z)-alkene in 86% yield and as a single geometric isomer.…”
Section: Reactionsmentioning
confidence: 99%
See 1 more Smart Citation